Mediterranean diet and hypertension: relationship between adherence to a Mediterranean diet and arterial hypertension - Mario Daidone; Tiziana Di Chiara; Alessandro Del Cuore; Alessandra Casuccio; Giovanni Salamone; Domenico Di Raimondo; Antonino Tuttolomondo (BMC Nutrition)
Abstract Background and aims No study has examined the relationship between the presence of hypertension and the Mediterranean diet (MeDi) concerning other cardiometabolic risk factors. We conducted a retrospective study to evaluate the presence of lower adherence to the Mediterranean diet in hypertensive subjects and analyze the correlation between adherence to the Mediterranean Diet and other cardiovascular risk factors. Materials and methods We analyzed the records and collected the data of the patients admitted to our Internal Medicine ward from 2010 to 2020 with a discharge diagnosis of metabolic syndrome according to the NCEP ATP-III criteria. We divided patients in two groups: hypertensive and no hypertensive. The Mediterranean Diet Score was used to evaluate the consumption and frequency of the foods characterizing a Mediterranean-type diet. Results Hypertensive patients were older (73 ± 11.5 vs. 57.2 ± 5.7; p < 0.0005) and had a higher mean BMI (29.9 ± 5.2 vs. 25 ± 2.4, p < 0.0005) compared to control group. The degree of adherence to the Mediterranean diet, evaluated by the Mediterranean diet score (MDS), was significantly higher in the control group than in the hypertensive group (3.8 ± 1.6 vs 6.9 ± 1.5; p < 0.0005). Various comorbidities were more prevalent in hypertensives, such as type 2 diabetes mellitus, heart failure, ischemic heart disease, and chronic renal failure. Lower adherence to the Mediterranean diet was significantly associated with an increased prevalence of dyslipidemia, cardiovascular diseases, chronic renal insufficiency, and PAD/carotid atherosclerosis, and significantly worse lipid profiles. Conclusion Our findings show that a lower adherence to a Mediterranean Diet Style is associated with a worse cardiovascular risk factor profile in hypertensive patients. Thus, Mediterranean diet adherence in hypertensive subjects is associated with a wider cardiometabolic scenario.